Point of care testing for infectious disease: ownership and quality. (23rd September 2021) - Lisby, Jan Gorm; Schneider, Uffe Vest
Abstract: Traditionally, diagnosis of acute infections has been organism-growth based, which makes timely and actionable infection diagnosis a major challenge. In addition, traditional microbial detection methods, including direct microscopy, are not suited for outsourcing to clinical, non-laboratory-educated personnel. Optimal management of patients with known or suspected clinical infections, such as targeted (or no) antimicrobial treatment and correct use of single room contact isolation facilities, requires rapid identification of the causative infectious microorganism. We are now facing a new disruptive paradigm shift in diagnostic microbiology. The availability of small-footprint robust instruments with easy-to-use assay kits allows non-laboratory-trained nurses and physicians to perform high-quality molecular diagnostics in a near-patient setting with results available in <30 minutes. This technology is currently breaking the centralized laboratory monopoly on the delivery of gold-standard clinical microbiology diagnostics. There is clear potential for huge positive impacts on clinical patient management and antibiotic stewardship, especially in settings where access to timely laboratory test results is not possible, but there are also potentially huge risks. Moving diagnostic testing away from the controlled diagnostic laboratory environment will lead to risks such as increased risk of inappropriate use of the diagnostic tests, insufficient training of staff performing the tests, incorrect interpretation of the test results, lack of quality control procedures, failure to capture test results in electronic patient records and compromised local as well as national surveillance. To reap the upside and avoid the downside of point-of-care infectious disease testing, the diagnostic laboratory needs to maintain oversight, and each institution must have a clear strategy for implementation and execution. If we fail, the risks could outweigh the benefits.